Thoracolumbar fascia ultrasound shear strain differs between low back pain and asymptomatic individuals: expanding the evidence - Norio Tomita; Marie-Hélène Roy-Cardinal; Boris Chayer; Stacey Daher; Ameer Attiya; Aline Boulanger; Nathaly Gaudreault; Guy Cloutier; Nathalie J. Bureau (Insights into Imaging)
Abstract Objectives To compare thoracolumbar fascia (TLF) shear strain between individuals with and without nonspecific low back pain (NSLBP), investigate its correlation with symptoms, and assess a standardized massage technique’s impact on TLF shear strain. Methods Participants were prospectively enrolled between February 2021 and June 2022. Pre- and post-intervention TLF ultrasound and pain/disability questionnaires were conducted. Cumulated (C|ShS|L) and maximum (Max|ShS|L) shear strain parameters were computed from radiofrequency data, and TLF thickness was measured on reconstructed B-mode images. Statistical analysis included linear mixed-effects regression. Results Thirty-two NSLBP participants (mean age, 57 ± 9 years [standard deviation]; 21 women) and 32 controls (51 ± 10 years; 22 women) (p = 0.02) were enrolled. The mean shear strain was higher in NSLBP participants (C|ShS|L: 327.1% ± 106.0 vs 290.2% ± 99.8, p < 0.0001; Max|ShS|L: 8.1% ± 2.8 vs 7.0% ± 2.4, p < 0.0001) than controls, while mean TLF thickness (1.6 mm ± 1.0 vs 1.5 mm ± 0.9; p = 0.43) was comparable. Elastography parameters correlated with pain [C|ShS|L estimate [β], 0.01 [95% CI: 0.002, 0.02]; p = 0.02); Max|ShS|L [β], 0.003 [95% CI: 0.001, 0.005]; p < 0.001)] and disability [C|ShS|L [β] 0.02 [95% CI: 0.005, 0.03]; p = 0.009); Max|ShS|L [β] 0.003 [95% CI: 0.001, 0.006]; p = 0.002)] scores. Neither C|ShS|L (β, 0.13 [−0.27, 0.53]; p = 0.53) nor Max|ShS|L (β, −0.02 [−0.10, 0.05]; p = 0.59) changed post-intervention. Conclusion Individuals with NSLBP demonstrated elevated TLF shear strain compared to controls, with similar TLF thickness. The shear strain correlated with pain and disability scores, yet a brief massage did not influence shear strain. Trial registration Clinicaltrials.gov, NCT04716101. Registered 14 January 2021, https://clinicaltrials.gov/study/NCT04716101 . Critical relevance statement Ultrasound shows elevated TLF shear strain in lower back pain sufferers compared to controls. This correlates with symptoms, suggesting a role as a pain generator. Further investigation into its anatomy, mechanical characteristics, and pathophysiology is crucial for better understanding. Key Points Structural and mechanical alterations of the TLF may contribute to low back pain. Elevated TLF lateral shear strain was found in patients with NSLBP. A brief standardized massage therapy technique did not influence elastography parameters. Graphical Abstract